Variations in food and drink advertising in UK monthly women's magazines according to season, magazine type and socio-economic profile of readers: a descriptive study of publications over 12 months - White Martin; Simpson Emma; Adams Jean (BMC Public Health, 2011)
Abstract Background Overweight and obesity are recognised nationally and internationally as key public health challenges. Food and drink advertising is one of the array of factors that influence both diet and physical activity choices and, hence, body weight and obesity. Little previous work has focused on food and drink advertising in magazines. We studied food and drink advertising in a wide range of popular UK monthly women's magazines published over a full year. We explored differences in the prevalence of food and drink advertising and the type of food and drinks advertised according to season, magazine type and socio-economic profile of readers. Methods All advertisements in all issues of 18 popular UK monthly women's magazines published over 12 months were identified. For each food or drink advertisement, branded food and drinks were noted and categorised into one of seven food groups. All analyses were at the level of the individual advertisement. Results A total of 35 053 advertisements were identified; 1380 (3.9%) of these were for food or drink. The most common food group represented was 'food and drinks high in fat and/or sugar' (28.0% of food advertisements), the least common group was 'fruits & vegetables' (2.0% of food advertisements). Advertisements for alcohol accounted for 10.1% of all food advertisements. Food and drink advertisements were most common in summer, general interest magazines, and those with the most affluent readerships. There were some differences in the type of food and drink advertised across season, magazine type and socio-economic profile of readers. Conclusions Food and drink advertisements represented only a small proportion of advertisements in UK women's monthly magazines. Food and drink advertisements in these magazines feature a high proportion of 'less healthy' foods. There were a number of differences across season, magazine type and according to the socio-economic profile of readers in the prevalence of food and drink advertisements. Fewer differences were seen in the type of food and drinks advertised.